Insulin-Related Peptide 5 is Involved in Regulating Embryo Development and Biochemical Composition in Pea Aphid with Wing Polyphenism - Guo, Shan-Shan; Zhang, Meng; Liu, Tong-Xian (Frontiers in Physiology, 2016)
In aphids there is a fecundity-dispersal trade-off between wingless and winged morphs. Recent research on the molecular mechanism of wing morphs associated with dispersal reveals that insulin receptors in the insulin signaling (IS) pathway regulate alteration of wing morphs in planthoppers. However, little is known about whether genes in the IS pathway are involved in developmental regulation in aphid nymphs with different wing morphs. In this study, we show that expression of the insulin-related peptide 5 gene (Apirp5) affects biochemical composition and embryo development of wingless pea aphids, Acyrthosiphon pisum. After comparing expression levels of major genes in the IS pathway between third instar winged and wingless nymphs, we found that Apirp5 showed higher expression in head and thorax of the wingless nymphs than in the winged nymphs. Although microinjection treatment affects physical performance in aphids, nymphs with RNA interference of Apirp5 had less weight, smaller embryo size and higher carbohydrate and protein contents compared to control group. Comparison between winged and wingless nymphs showed a similar trend. These results indicate that Apirp5 is involved in embryo development and metabolic regulation in wing dimorphic pea aphid.